Going public abroad - Caglio, Cecilia; Hanley, Kathleen Weiss; Marietta-Westberg, Jennifer (Journal of Corporate Finance, 2016)
We examine the decision of a firm to go public abroad and list securities outside their country of origin. Foreign IPO issuers are more likely to choose a global underwriter but only if the home country is less financially integrated. We find that the probability of conducting a foreign IPO is higher if the home country has a less developed stock market, its disclosure regime is weaker and is less financially integrated. Using a matched sample, we show that foreign IPOs raise more capital than their domestic counterparts. Finally, the determinants of the choice of a US listing are unique. Our results suggest that the rise of global underwriters facilitates the movement of capital across nations and contributes to world financial globalization.